Selective Surface and Intraluminal Localization of Wnt Ligands on Small Extracellular Vesicles Released by HT-22 Hippocampal Neurons - Torres, Viviana I.; Barrera, Daniela P.; Varas-Godoy, Manuel; Arancibia, Duxan; Inestrosa, Nibaldo C. (Frontiers in Cell and Developmental Biology, 2021)
The Wnt signaling pathway induces various responses underlying the development and maturation of the nervous system. Wnt ligands are highly hydrophobic proteins that limit their diffusion through an aqueous extracellular medium to a target cell. Nevertheless, their attachment to small extracellular vesicles-like exosomes is one of the described mechanisms that allow their transport under this condition. Some Wnt ligands in these vehicles are expected to be dependent on post-translational modifications such as acylation. The mechanisms determining Wnt loading in exosomes and delivery to the target cells are largely unknown. Here, we took advantage of a cell model that secret a highly enriched population of small extravesicular vesicles (sEVs), hippocampal HT-22 neurons. First, to establish the cell model, we characterized the morphological and biochemical properties of an enriched fraction of sEVs obtained from hippocampal HT-22 neurons that express NCAM-L1, a specific exosomal neuronal marker. Transmission electron microscopy showed a highly enriched fraction of exosome-like vesicles. Next, the exosomal presence of Wnt3a, Wnt5a, and Wnt7a was confirmed by western blot analysis and electron microscopy combined with immunogold. Also, we studied whether palmitoylation is a necessary post-translational modification for the transport Wnt in these vesicles. We found that proteinase-K treatment of exosomes selectively decreased their Wnt5a and Wnt7a content, suggesting that their expression is delimited to the exterior membrane surface. In contrast, Wnt3a remained attached suggesting that it is localized within the exosome lumen. On the other hand, Wnt-C59, a specific inhibitor of porcupine O-acyltransferase (PORCN), decreased the association of Wnt with exosomes, suggesting that Wnt ligand acylation is necessary for them to be secreted by exosomes. These findings may help to understand the action of the Wnt ligands in the target cell, which could be defined during the packaging of the ligands in the secretory cell sEVs.